PERANAN KOMUNITAS DIGITAL SINGEL LENS REFLECT CINEMATOGRAPHY INDONESIA (DCI PEKANBARU) DALAM MENARIK MINAT SINEAS UNTUK MENGIKUTI FESTIVAL FILM - Aditya Sumija; Belli Nasution (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
Electronic Media Television is one medium that can display information in perfectly , which is a combination of audio and visual technology , so it can easily be accepted by the audience as a communicant . With the perfection of which is owned by the television media , interest communicant to choose this medium is greater than the other mass media such as radio , newspapers , and movies . The messages conveyed through the medium of television pictures and sound simultaneously , live , fast , real-time , and can reach a very spacious room . Understanding filmmakers about cinemas, that are adequate but did not get support to develop their work with a wide audience . It makes filmmakers in Indonesia trying to attend the festival which is held metro tv. Besides become famous, sineas are also filmmakers received support facilities in making a documentary flim and get in-depth education cinema.The method used in this research is qualitative method. Data collection techniques in this study using interviews . The location of this research will be carried out at the office of Digital Single Lens Reflect Cinematography Indonesia ( DCI Pekanbaru ) Jalan Cendrawasih No. 23 , Tangkerang , Pekanbaru . Subjects in this study are community members Cinematography Digital Single Lens Reflect Indonesia ( DCI pekanbaru ) , while objects in the study in this research is the interest of filmmakers follow the film festival . For data analysis , researchers used a method of interactive analysis and Hubberman Miles . As for checking the validity of the data , researchers used data triangulation technique.The results showed that the activity is the community DSLR Cinematography Indonesia (DCI Pekanbaru) in attracting filmmakers follow the film festival include the extension and various activities throughout high school in the city of Pekanbaru, Obstacles facing the community DSLR Cinematography Indonesia (DCI Pekanbaru) in attracting filmmakers follow the film festival among others, issues of time constraints, where filmmakers and the member of the community has its own activities beyond their duties as members. Besides the lack of adequate equipment help to produce good work also affect the interest of Sines in making a film work. Limited information about the film for filmmakers who want produce work by following the film festival, an important area in the filmmaker's interest, it is because information is the main weapon in the levy of a media, especially cinema.Keywords : Media, Television, Sineas